Priest of bones - McLean, Peter, 1972- (ACE, 2018)
The war is over, and army priest Tomas Piety heads home with Sergeant Bloody Anne at his side. But things have changed while he was away: his crime empire has been stolen and the people of Ellinburg--his people--have run out of food and hope and places to hide. Tomas sets out to reclaim what was his with help from Anne, his brother, Jochan, and his new gang: the Pious Men. But when he finds himself dragged into a web of political intrigue once again, everything gets more complicated. As the Pious Men fight shadowy foreign infiltrators in the back-street taverns, brothels, and gambling dens of Tomas's old life, it becomes clear: The war is only just beginning.